Lazarettos , Tebhırhane And Tahaffuzhane Buıldıngs - Sedes , Fatma (Architecture Image Studies, 2021)
Due to the international maritime trade and transportation that developed in the Ottoman Empire and whole World at the 18th and 19th centuries, the risk and possibility of disease transmission increased. The Ottoman government took measures against infectious diseases by carrying out significant studies on diseases such as cholera and plague. In addition to the cholera epidemic in 1835, the plague danger and epidemic were on the agenda. Vessels were quarantined for 20-25 days in these laboratories (lazarettos) in order to control epidemic diseases.. Outbreaks of plague were seen in 1586, 1590, 1592 and 1599 (İnalcık, 1973: 243; Lowry, 2003: 126) . For more than 300 years (from 1500 to 1800), some regions of the Ottoman Empire in 1778, one-fifth of the population of Istanbul succumbed to the plague.In the 1780s, the daily death of the people of Istanbul from the plague exceeded the number of 1000.In 1792, the plague epidemic was at its peak. European travelers and diplomats recorded 3000 deaths a day in Istanbul. According to the information obtained, William Wittman, a surgeon affiliated to the British Military Mission in Istanbul, reported that 30-40 people died from plague every day during the summer season in Çanakkale in 1798 (Robarts, 2010: 188, 189). The people of İzmir have suffered greatly, as it is a large port city that is in constant contact with the world. Other epidemics and plague recurring in more than half of the century have surrounded the environment (Quataert, 2005: 114). In 1838, Mahmud II, who wanted to protect the sea routes from contagious epidemics, established a committee called Meclis-i Tahaffuz to supervise the quarantine measures and establish a delicacy in the Bosphorus. (Abou-Hodeib, 2007: 227). In this study, the ‘’lazarettos ,tebhirhane and tahaffuzhane’’ buildings established in United States of America , European countries including Istanbul are examined.It is known that preventing the spread of epidemics has gained importance in the past years, and it is emphasized by medical historians. M.S.7. In the 19th century, Emperor Justinian tried to quarantine those who came by sea from countries with plague epidemics so that they would not interfere with the people of the city. The first Christian hospitals, IV. It was established in Istanbul in the century (N. Yıldırım). In addition, it is known that hospitals were established in the cities of Urfa (Edessa), Kayseri (Kaisareia) and Sivas (Sebasteia). Religious hospitals, which were opened in Istanbul and functioned as shelters, have become modern hospitals in historical development. They claim that the concept of scientific hospital developed from the Byzantine period Istanbul hospitals. VIII. by the Umayyad caliph al-Walid. It is emphasized that it was founded in the century. Empress Helena had a hospital established in Istanbul right after Constantine I closed the asclepions. In the letter he wrote to the Archpriest of Galata, Arsakios, the Emperor ordered that an institution be established in each city for the poor and the sick, the expenses of which would be met from the public revenues Empress Irene, VIII. He built a new hospital at the end of the century. Emperor Theophilos (829-842), who took him as an example, ordered the construction of a hospital designed for the patients to benefit from the fresh air carried by the gentle winds and to see the beautiful view of the Bosphorus. He saw the improvement of the city walls and the establishment of this hospital as his most important gift to the people of Constantinople. From this period, the construction of a hospital became one of the leading services of the emperors. XI. By the 19th century, the number of hospitals in Istanbul had reached 35. These are II. The hospital with the same name was added around the Tessares Martyrs (Forty Martyrs) Church, which was founded by Isaakios (1185-1195) on Mese (Divanyolu) Street. According to Prokopios; Sampson, VI. He was a benevolent folk physician who lived more than a century ago, dedicating his home to the seriously ill and foreigners. Evliya Çelebi says that there is a wood warehouse of Matbah-ı Âmire in this area. As a matter of fact, during the cleaning works that started in 2009 next to Hagia Irene, the weights of the giant wood scales depicted in Hünernâme were found. The remains unearthed next to Hagia Irene are thought to belong to St. Sampson Xenon. Sampson (d. 530), a benevolent folk physician, in his house near Hagia Sophia to serve God; He cared for the helpless, the sick, and homeless strangers. After curing Justinian I (527-565), who fell ill for a while, the emperor enlarged and rebuilt Sampson’s house and named it after Sampson. Although the house was completely destroyed like other buildings of the city during the Nikea Revolt (11-19 January 532), it was repaired with the generous donation of the emperor. VI. In the 16th-century source, The Life Story of St. Artemios, there is a mention of an operation performed in the eye clinic of this well-organized hospital. Xenodokyum, or simply xenon, was the general name of social welfare institutions/campaigns with housing for the poor and orphans, a hospital, an old and poor house, an orphanage and a leprosy house. After that, a group of buildings where the sick and the helpless were cared for began to be built. In these settlements built in Istanbul, there were Nosokomeion (hospital where the sick are treated), brefotrophion (hospice for children left on the street), orfanotrophion (orphanage), ptokhokomeion (home for the poor), gerontokomeion (home for the elderly) and VII. Between the centuries, many xenon were made in Istanbul.